Temporal changes in urban green space based on normalized difference vegetation index - Ahmad, Asmala; Mohd Aboobaider, Burhanuddin; Mohamad Isa, Mohd Sa'ari; Md Hashim, Noorazuan; Rosul, Mochamad; Muhamad, Sulong; Man, Shamsuddin (Hikari Ltd, 2014)
This study identifies land use changes in the metropolitan region of Klang-Langat Valley focusing on urban sprawl and green space. A technique called Normalized Difference Vegetation Index (NDVI) is used to quantify temporal urban green space dynamics. All districts in the valley recorded a marked increase in urban area, but decreased in agriculture and forest areas. Result of vegetation index analysis showed that NDVI increases for water body, bare soil, and built-up area category for as much as 16.98% from 1998 to 2001, but during the same period vegetation experience a decrease of 22.25%.